Current Status and Future Perspectives in Articles about Coding Learning at Pre-University Level Published from 2009 to 2017: A Content Analysis Study (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In recent years, remarkable attention has been paid to coding and computer programming learning and teaching at pre-university level. Many countries are taking important steps in this field every passing year. Examining the studies on coding learning enriched by use of different tools based on specific periods may be guiding for researchers in this field, in which there is an ever-growing interest. In this regard, the purpose of this study is to make a thorough examination of the articles on coding learning and teaching at pre-university level published in international journals from 2009 to 2017 and to show the general trend. The study examined 34 articles published in this field from 2009 to 2017 through content analysis. The data collected by use of Article Classification Form were descriptively analyzed. The research findings show that most articles published in this field covered robotic tools at elementary education level. They also indicate that quantitative – quasi-experimental method was the most preferred method, and various data collection tools, achievements tests being in the first place, were employed. The majority of studies reached positive results from different perspectives while few studies reported neutral results. The results of the present study are considered to be revealing the current situation in this field and lighting the way for other studies to be carried out in the future.